Approaches to Biofunctionalize Polyetheretherketone for Antibacterial: A Review - Wang, Yihan; Zhang, Shutao; Nie, Bin’en; Qu, Xinhua; Yue, Bing (Frontiers in Bioengineering and Biotechnology, 2022)
Due to excellent mechanical properties and similar elastic modulus compared with human cortical bone, polyetheretherketone (PEEK) has become one of the most promising orthopedic implants material. However, implant-associated infections (IAI) remain a challenging issue since PEEK is bioinert. In order to fabricate an antibacterial bio-functional surface, modifications of PEEK had been widely investigated. This review summarizes the modification strategies to biofunctionalize PEEK for antibacteria. We will begin with reviewing different approaches, such as surface-coating modifications and controlled release of antimicrobials. Furthermore, blending modifications and 3D printing technology were discussed. Finally, we compare the effects among different approaches. We aimed to provide a in-depth understanding of the antibacterial modification and optimize the design of PEEK orthopedic implant.